Fish Fingerlings: Purchasing, Transporting, and Stocking - Michael McGee; Charles E. Cichra (EDIS)
Finding a source of fish fingerlings (young fish) is the first step towards successful fish production. Following that, transporting the fish, and proper stocking procedures are necessary. Some of the most important considerations relating to fingerling purchasing, transporting, and stocking are reviewed in this document. First published June, 1991